Features of Muscle Tissue Microstructure of Cattle in Industrial Agglomerations under the Environmental Pressure Conditions - I. Vasilenko, Lyudmila; Grebenshchikov, Andrey V.; Danyliv, Maksim M.; Vasilenko, Olga A.; Ozherelyeva, Olga N. (KnE Life Sciences, 2019)
The intensive development of the industrial sector, intensification of the agro-industrial complex, associated with the use of various fertilizers, active use of modern household chemicals lead to the constant increase in xenobiotics in the environment in both rural and urban agglomerations. There are settlements and farms within the industrial areas, therefore, the issue of accumulation of ecotoxicants in the organs and tissues of an animal, as well as the impact on the state of its health, is of particular importance. In the regions with tough environmental situation associated with anthropogenic contamination, xenobiotics of anthropogenic origin can directly or indirectly modify the activity of various body systems. The integral characteristic that reflects adaptive modifications of biota is the morphological and functional status of organs and tissues of an animal, including the state of muscle tissue. An analysis of the regenerative plastic potential of muscle tissue allows finding innovative approaches to assessing the effects of environmental impacts on animals. Up to the present day, the morphological and functional characteristics of muscle tissue in young animals and adult cattle have not been sufficiently studied in the conditions of the tough environmental situation of the Central Federal District of the Russian Federation. The issue of ecological pathologies of organs in productive animals is quite urgent for the territory of the Central Federal District with its developed agro-industrial complex and industry. The study of animals from the agglomeration of the large chemical plant showed that cattle react differently to pollutants. The animals demonstrated changes not only in hematological and biochemical parameters, but also in the morphological and functional status of muscle tissue.